PROTOTYPING A SENSOR ENABLED 3D CITYMODEL ON GEOSPATIAL MANAGED OBJECTS - E. Kjems; J. Kolář (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
One of the major development efforts within the GI Science domain are pointing at sensor based information and the usage of real time information coming from geographic referenced features in general. At the same time 3D City models are mostly justified as being objects for visualization purposes rather than constituting the foundation of a geographic data representation of the world. The combination of 3D city models and real time information based systems though can provide a whole new setup for data fusion within an urban environment and provide time critical information preserving our limited resources in the most sustainable way. Using 3D models with consistent object definitions give us the possibility to avoid troublesome abstractions of reality, and design even complex urban systems fusing information from various sources of data. These systems are difficult to design with the traditional software development approach based on major software packages and traditional data exchange. The data stream is varying from urban domain to urban domain and from system to system why it is almost impossible to design a complete system taking care of all thinkable instances now and in the future within one constraint software design complex. On several occasions we have been advocating for a new end advanced formulation of real world features using the concept of Geospatial Managed Objects (GMO). This paper presents the outcome of the InfraWorld project, a 4 million Euro project financed primarily by the Norwegian Research Council where the concept of GMO's have been applied in various situations on various running platforms of an urban system. The paper will be focusing on user experiences and interfaces rather then core technical and developmental issues. The project was primarily focusing on prototyping rather than realistic implementations although the results concerning applicability are quite clear.